Wpływ zalesienia zlewni na temperaturę wody w rzece - Ptak, Mariusz (Leśne Prace Badawcze, 2017)
The objective of this paper was to analyse the effects of catchment area forestation on the temperature of river waters. Two rivers, Czerna Wielka and Szprotawa, were covered in this research project and both are located in south-west Poland, running through the largest compact forest complex in the country, Bory Dolnośląskie. Both of the rivers are located within the same climatic region, and are similar in terms of their hydrology. Land use in the catchment area however is very diverse with 71.6% forest cover in the case of the Czerna Wielka River and direct contact of the forest with the river occurs over 68.3% of its length. For the Szprotawa River, the indices amount to only 39.3% and 21.6%, respectively. Data on the daily water temperatures for both of the rivers were obtained from the Hydrological Yearbooks of Surface Waters for the period 1969–1983. The mean annual water temperature in the analysed period in the case of the Czerna Wielka River amounted to 8.0°C, and in the case of the Szprotawa River it equalled 9.2°C. During the cooler half of the year (November-April), the mean water temperature for the entire examined period amounted to 3.8°C for Czerna Wielka, and 3.6°C for Szprotawa. Higher variability was recorded for the warmer seasons (May-October), where mean temperatures amounted to 12.1°C and 14.7°C, respectively. The obtained results concur with other similar research conducted around the world, and in the context of climate change are of practical value. The important role of forests in the moderation of thermal conditions is evidently unquestionable. Therefore, minimising the impact of unfavourable climatic changes on river ecosystems and their surroundings requires striving for appropriate forest management in the near-bank (buffer) zone along banks of both larger rivers and their tributaries.